A comparative transcriptomic approach to elucidate common and divergent mechanisms involved in apricot and peach fruit development and ripening - Ziliotto, Fiorenza; Rasori, Angela; Manganaris, George A. (My University, 2010)
Transcript profiling methods are increasingly used to understand the biological basis of growth and development, and fruit quality in the case of fruits. Such methods provide information for thousands of genes, including those of still unknown function. Furthermore, high-throughput methodologies can be used for comprehensive transcriptome analyses, which may lead to further elucidation of fruit growth and development. Microarray is an attractive genomic tool, since it can be used in a heterologous fashion for gene discovery and characterization in species where few resources are available. In the current study, the progress of apricot (Prunus armeniaca cv. Goldrich) fruit ripening during the last developmental stages was monitored and microarray data that were produced were used for comparative in silico studies with data reported during the transition of peach and nectarine fruits from pre-climacteric to climacteric stage. Transcriptomic studies for both fruit species were carried out using the first available peach microarray (μPEACH 1.0) that contains 4,806 oligonucleotides, each corresponding to a single unigene. Intriguingly, a sharp increase of transcript levels in genes regulating an array of heat shock proteins was detected in apricot fruit, which was not the case during nectarine fruit ripening. In addition, we focused on transcript levels of auxin regulated proteins and their role during the last phases of fruit ripening. Overall, data of the present study offers an initial descriptive picture of transcript profiling of novel key genes and their putative role during the last stages of fruit development is challenged. A future perspective, which will also encompass data validation for genes of interest, is the unravelling of the mechanisms underlying the ripening process in stone-fruits, through the identification of genes differentially expressed during peach and apricot ripening and their correlation with traits of agronomic interest
Keywords: Apricot; Peach; Rosaceae; Prunus; Fruit--Development; Fruit--Ripening; Nucleic acid hybridization; Genomics; Messenger RNA; Heat shock proteins; Gene expression